Tradisi Penentuan Hari Baik Dalam Pernikahan Perspektif ‘Urf: - Mohamad Falih; Ahmad Rezy Meidina (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This research will examine one of the traditions that prevail in the Lebaksiu sub-district community, Tegal district, namely the tradition of calculating and determining auspicious days at marriage. This research is a field research (Field Research), while data collection techniques using observation, interviews, and documentation. The type of approach used in this study is a sociological approach, this approach is used to find out how the process of determining a wedding day in Javanese primbon and how the Urf perspective relates to determining a good day in marriage carried out by the Lebaksiu community, Tegal district. The results of this research show that the tradition of determining a good day in marriage that occurs in the Lebaksiu sub-district based on Javanese Primbon is considered valid or permissible if only as a form of endeavor to reject mafshadatan and for stability of the heart without cultizing the day, date, month or the embodiment of the Primbon. however, if there is a cult towards him then this is tahayur, where the action is contrary to Islamic law and makes it 'urf fasid. Keywords: determination of auspicious days, wedding, urf